A Single Center Experience of Abdominal Wall Graft Rejection After Combined Intestinal and Abdominal Wall Transplantation. Issue 8 (9th July 2013) - Allin, B. S. R.; Ceresa, C. D. L.; Issa, F.; Casey, G.; Espinoza, O.; Reddy, S.; Sinha, S.; Giele, H.; Friend, P.; Vaidya, A.
Abstract: We report our outcomes following combined intestinal and abdominal wall transplantation, focusing on the presentation and treatment of acute rejection of the abdominal wall vascularized composite allograft (VCA). Retrospective analysis of all patients with combined intestinal/VCA transplantation was undertaken. Graft abnormalities were documented photographically and biopsies taken, with histological classification of rejection according to Banff 2007 guidelines. We have performed five combined intestinal and abdominal wall transplants to date. Two patients developed erythematous, maculopapular to papular eruptions confined to the VCA, histologically confirmed as grade II/III rejection, yet with normal bowel on endoscopy. Both patients' rashes resolved within 72 h of increasing immunosuppressive treatment. One patient later developed a recurrence of the rash, confirmed as skin rejection, but did not immediately seek medical attention. Treatment was therefore delayed, and mild intestinal rejection developed. We describe the rash associated with VCA rejection, and propose that while the skin of an abdominal wall VCA may reject independently of the intestinal allograft, delay in treatment of rejection episodes may result in rejection of the intestinal graft. Abstract : In a retrospective analysis of patients undergoing combined intestinal and abdominal wall transplantation, an erythematous maculopapular rash occurring prior to rejection of the intestinal component is identified as the presenting feature of rejection of the abdominal wall.